Computational Methods for Electromagnetic and Optical Systems, Second Edition. - Jarem, John M. (Optical Science and Engineering., 2014)
Praise for the First Edition "" ... a small but formidable book which rigorously sets out the basic theory, provides useful illustrative problems and directs the reader to relevant further reading from the excellent reference lists. The book is directed towards graduate students and researchers but selected sections would provide valuable undergraduate teaching material. It is the type of wide-ranging reference book that will find its way onto many bookshelves and, over the years, will become well-worn from frequent use.""--ProfBooks.com, 2001.